Cone-rod homeobox CRX controls presynaptic active zone formation in photoreceptors of mammalian retina. (10th August 2018) - Assawachananont, Juthaporn; Kim, Soo-Young; Kaya, Koray D; Fariss, Robert; Roger, Jerome E; Swaroop, Anand
Abstract: In the mammalian retina, rod and cone photoreceptors transmit the visual information to bipolar neurons through highly specialized ribbon synapses. We have limited understanding of regulatory pathways that guide morphogenesis and organization of photoreceptor presynaptic architecture in the developing retina. While neural retina leucine zipper (NRL) transcription factor determines rod cell fate and function, cone-rod homeobox (CRX) controls the expression of both rod- and cone-specific genes and is critical for terminal differentiation of photoreceptors. A comprehensive immunohistochemical evaluation of Crx −/− (null), Crx Rip/+ and Crx Rip/Rip (models of dominant congenital blindness) mouse retinas revealed abnormal photoreceptor synapses, with atypical ribbon shape, number and length. Integrated analysis of retinal transcriptomes of Crx -mutants with CRX- and NRL-ChIP-Seq data identified a subset of differentially expressed CRX target genes that encode presynaptic proteins associated with the cytomatrix active zone (CAZ) and synaptic vesicles. Immunohistochemistry of Crx -mutant retina validated aberrant expression of REEP6, PSD95, MPP4, UNC119, UNC13, RGS7 and RGS11, with some reduction in Ribeye and no significant change in immunostaining of RIMS1, RIMS2, Bassoon and Pikachurin. Our studies demonstrate that CRX controls the establishment of CAZ and anchoring of ribbons, but not the formation of ribbon itself, in photoreceptor presynaptic terminals.